Evaluation of heat transfer in a catalytic fixed bed reactor at high temperatures - JORGE,L. M. M. (1999)
Experimental results of fixed-bed heat-transfer experiments with no chemical reaction are presented and discussed. The runs were carried out in a tubular integral reactor heated by an electrical furnace at temperatures in the range of 100 to 500°C. Experimental temperature profiles were determined for the electrical furnace, for the reactor wall, and for the fixed bed center. Industrial catalyst for the prereforming of hydrocarbons was employed as the packing material. The effects of process conditions (furnace temperature, gas flow rate) on the heat-transfer coefficients were evaluated. The experimental results were analyzed in terms of the external, wall, and internal thermal resistances, associated in series, and compared with model predictions. Under the conditions studied, the overall coefficient was mostly a function of the external effective heat-transfer coefficient. An alternative data treatment was proposed to determine the internal heat-transfer coefficient in fixed beds when wall temperature is not constant.